Service process design and/or redesign by fusing the powers of Design for Six Sigma and Lean. (5th September 2007) - Chang, Che-Ming; Su, Chao-Ton
In today's booming service economy, providing customers with high-quality and quick services has been widely recognised as an essential means of achieving business excellence. To attain a higher quality level of service than the competitor in the market, Design for Six Sigma (DFSS) has been developed as a breakthrough strategy for service process design and/or redesign, which is fundamental to the delivery of service quality to the customer. Meanwhile, a faster time-to-market capability of service can be obtained through utilising the speed advantage of Lean. Therefore, it is the motivation of this paper for researching that DFSS when combined with Lean can be synergistic in the upfront design phases of the service development process. In addition, a methodology that integrates the individual benefits of DFSS and Lean was developed, and a case study of software development process was conducted to examine the effectiveness of the methodology.